2010
DOI: 10.1210/en.2009-0546
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Amylin/Leptin Synergy in Rodent Models

Abstract: The present studies aimed to identify mechanisms contributing to amylin/leptin synergy in reducing body weight and adiposity. We reasoned that if amylin/leptin harnessed complementary neuronal pathways, then in the leptin-sensitive state, amylin should augment leptin signaling/binding and that in the absence of endogenous amylin, leptin signaling should be diminished. Amylin (50 microg/kg, ip) amplified low-dose leptin-stimulated (15 microg/kg, ip) phosphorylated signal transducer and activator of transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
154
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(172 citation statements)
references
References 33 publications
15
154
2
1
Order By: Relevance
“…Means with different letters are significantly different (p<0.05), whereas means with the same letters are not different from each other. A, amylin; C, non-treated control; L, leptin It has been proposed that co-administration of leptin and amylin in mice in vivo results in a multiplicative effect on STAT3 phosphorylation in the hypothalamus as compared with treatment with either of the hormones separately [36]. Also, we have demonstrated for the first time that leptin and amylin increase STAT3/AMPK/ERK signalling and that the effects of these two hormones are similar in magnitude, peaking at about the same time in mouse GT1-7 hypothalamic and C 2 C 12 muscle cell lines in vitro [35] and in human adipose tissues and peripheral blood mononuclear cells ex vivo [30].…”
Section: Discussionmentioning
confidence: 99%
“…Means with different letters are significantly different (p<0.05), whereas means with the same letters are not different from each other. A, amylin; C, non-treated control; L, leptin It has been proposed that co-administration of leptin and amylin in mice in vivo results in a multiplicative effect on STAT3 phosphorylation in the hypothalamus as compared with treatment with either of the hormones separately [36]. Also, we have demonstrated for the first time that leptin and amylin increase STAT3/AMPK/ERK signalling and that the effects of these two hormones are similar in magnitude, peaking at about the same time in mouse GT1-7 hypothalamic and C 2 C 12 muscle cell lines in vitro [35] and in human adipose tissues and peripheral blood mononuclear cells ex vivo [30].…”
Section: Discussionmentioning
confidence: 99%
“…81 The effect of the amylin/leptin combination on energy balance appeared to be paralleled by a preferential oxidation of fat as indicated by the low respiratory quotient in both the amylin/leptin and pair-fed groups; 81,[84][85][86] importantly, the lower respiratory quotient was still evident in amylin/leptin coinjected animals during the weight stable phase and not only during weight loss like in the pair-fed group. 81,85,[90][91][92] All effects combined, the amylin/leptin combination treatment prevented the suppression of energy metabolism that is typically seen in situations of negative energy balance which may, for example, be induced by simple dieting. The potential mechanisms of this interaction have been summarized recently.…”
Section: Interactions Of Amylin With Other Factors Involved In the Comentioning
confidence: 95%
“…Amylin strongly enhanced leptin signaling specifically in the ventromedial hypothalamus, and this was also confirmed under in vitro conditions. 81,85,[95][96][97] Amylin also increased leptin binding in the ventromedial hypothalamus and other hypothalamic sites, for example, the dorsomedial hypothalamus, 85 whereas leptin receptor expression was reduced in the mediobasal hypothalamus in amylin-deficient mice. 85 A recent study indicated that interleukin-6 (IL-6) seems to be involved in the leptin-sensitizing effect of amylin.…”
Section: Interactions Of Amylin With Other Factors Involved In the Comentioning
confidence: 99%
See 2 more Smart Citations